The Roles of The Headmaster’s Leadership Types in Overcoming The Students’ Violation - Andriani Tunnisa; Eka Damayanti; Baharuddin Baharuddin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
The headmaster, as the highest policymaker in the school, has a very important role in overcoming violations that occur in the schools. Successful headmaster can be seen from the process of influencing every element in the school and being able to apply all leadership models in any situation and condition. There are several types of leadership, namely; authoritarian, democratic, and charismatic. This study aims to determine the headmaster’s leadership types of MTs As'adiyah Ereng-ereng in overcoming the students’ violations. This was field research with qualitative methods where the data sources came from the headmaster, students, educators, and students who committed violations. The data were collected from interviews, observation, and documentation. Then they were analyzed with analysis through data reduction, data presentation, and conclusion. The results indicate that the forms of violations committed were (1) not praying in congregation, skipping the classes, not wearing appropriate uniforms, destroying facilities, and carrying cellphones. The leadership type that is most often applied in the schools was a charismatic leadership type. Although this type of dominates, democratic, and collective leadership is also found.